Fc‐Silent Anti‐CD154 Domain Antibody Effectively Prevents Nonhuman Primate Renal Allograft Rejection. Issue 5 (25th February 2017) - Kim, S. C.; Wakwe, W.; Higginbotham, L. B.; Mathews, D. V.; Breeden, C. P.; Stephenson, A. C.; Jenkins, J.; Strobert, E.; Price, K.; Price, L.; Kuhn, R.; Wang, H.; et al.
Abstract : The advent of costimulation blockade provides the prospect for targeted therapy with improved graft survival in transplant patients. Perhaps the most effective costimulation blockade in experimental models is the use of reagents to block the CD40/CD154 pathway. Unfortunately, successful clinical translation of anti‐CD154 therapy has not been achieved. In an attempt to develop an agent that is as effective as previous CD154 blocking antibodies but lacks the risk of thromboembolism, we evaluated the efficacy and safety of a novel anti‐human CD154 domain antibody (dAb, BMS‐986004). The anti‐CD154 dAb effectively blocked CD40‐CD154 interactions but lacked crystallizable fragment (Fc) binding activity and resultant platelet activation. In a nonhuman primate kidney transplant model, anti‐CD154 dAb was safe and efficacious, significantly prolonging allograft survival without evidence of thromboembolism (Median survival time 103 days). The combination of anti‐CD154 dAb and conventional immunosuppression synergized to effectively control allograft rejection (Median survival time 397 days). Furthermore, anti‐CD154 dAb treatment increased the frequency of CD4 + CD25 + Foxp3 + regulatory T cells. This study demonstrates that the use of a novel anti‐CD154 dAb that lacks Fc binding activity is safe without evidence of thromboembolism and is equally as potent as previous anti‐CD154 agents at prolonging renal allograft survival in a nonhuman primate preclinical model. Abstract : An Fc‐silent anti‐CD154 domain antibody safely and effectively promotes long‐term kidney transplant survival in nonhuman primates without the risk of thromboembolism when combined with a clinically relevant conventional immunosuppression regimen. See the editorial from Thomson and Ezzelarab onpage 1156 .